How long can nosocomial pathogens survive on textiles? A systematic review - Kampf, Günter (German Medical Science GMS Publishing House, 2020)
Aims: Healthcare-associated infections linked to contaminated textiles are rare but underline their potential role as a source for transmission. The aim of the review was to summarize the experimental evidence on the survival and persistence of the different types of nosocomial pathogens on textiles.Methods: A literature search was performed on MedLine. Original data on the survival of bacteria, mycobacteria, and fungi and persistence of viruses on textiles were evaluated.Results: The survival of bacteria at room temperature was the longest on polyester (up to 206 days), whereas it was up to 90 days for some species on cotton and mixed fibers. Only low inocula of 100 CFU were found on all types of textiles with a short survival time of ≤3 days. Most bacterial species survived better at elevated air humidity. The infectivity of viruses on textiles is lost much faster at room temperature, typically within 2-4 weeks.Conclusions: Contaminated textiles or fabrics may be a source of transmission for weeks. The presence of pathogens on the coats of healthcare workers is associated with the presence of pathogens on their hands, demonstrating the relevance of textile contamination in patient care.